Clinicohistopathological correlation of hysterectomy in rural India: an observational study - Gupta, Kumud; Parmar, Meennal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hysterectomy - abdominal or vaginal or laparoscopic assisted, hysterectomy is the most commonly performed elective major gynaecological surgery. Rate of hysterectomy has varied between 6.1 and 8.6/1000 women of all ages. The abdominal removal of the uterus is called ‘total abdominal hysterectomy’ while the removal of the uterus by the vaginal route is termed as ‘vaginal hysterectomy’. The supracervical removal of the uterus is termed as ‘subtotal hysterectomy’. As compared to a higher frequency of hysterectomy (10-20%) in other countries, a lower rate (4-6%) has been reported in India. Methods: The study was conducted in the department of obstetrics and gynaecology National Institute of Medical Sciences (NIMS), Jaipur in 2013-2014. 100 patients were undergoing hysterectomy. The patients were diagnosed on the basis of history, clinical examination and ultrasonography report. Results: In our study, maximum number of clinical diagnosis made, were of DUB (with PID and Prolapse) which was 35%. This was followed by leiomyoma i.e. 29%, clinically 29 cases were diagnosed of which 24 were histopathologically proven. Adenomyosis (10%), clinically 10 cases were identified but there were 15 cases histopathologically, this can be due to different clinical presentation. Clinically diagnosed cases of carcinoma endometrium and cervical erosions were 1% and 2% respectively. Overall sensitivity for clinical diagnosis in our study was 52%. The most common histopathological finding was leiomyoma (24%), followed by adenomyosis (15%) and chronic cervicitis (15%). Other pathologies include combined adenomyosis and leiomyoma (6%), benign ovarian cyst in four cases. Normal histopathological report was obtained in 32 cases. Maximum correlation (100%) was found with cancer cervix, cancer ovary and cancer endometrium. Conclusions: Hysterectomy still remains the widely used modality in developing as well as developed countries. Every hysterectomy specimen should be subjected to histopathological examination to ensure diagnosis and thus management in particular of malignant diseases.